Solve for y (4y)/3+2(3-y)=5

4y3+2(3-y)=5
Factor the equation.
Apply the distributive property.
4y3+2⋅3+2(-y)=5
Multiply 2 by 3.
4y3+6+2(-y)=5
Multiply -1 by 2.
4y3+6-2y=5
To write -2y as a fraction with a common denominator, multiply by 33.
4y3-2y⋅33+6=5
Combine -2y and 33.
4y3+-2y⋅33+6=5
Combine the numerators over the common denominator.
4y-2y⋅33+6=5
To write 6 as a fraction with a common denominator, multiply by 33.
4y-2y⋅33+6⋅33=5
Combine 6 and 33.
4y-2y⋅33+6⋅33=5
Combine the numerators over the common denominator.
4y-2y⋅3+6⋅33=5
Reorder terms.
-2⋅(3y)+4y+3⋅63=5
Rewrite -2⋅3y+4y+3⋅63 in a factored form.
Multiply -2 by 3.
-6y+4y+3⋅63=5
Multiply 3 by 6.
-6y+4y+183=5
-2y+183=5
Factor 2 out of -2y+18.
Factor 2 out of -2y.
2(-y)+183=5
Factor 2 out of 18.
2(-y)+2(9)3=5
Factor 2 out of 2(-y)+2(9).
2(-y+9)3=5
2(-y+9)3=5
2(-y+9)3=5
2(-y+9)3=5
Solve the equation.
Multiply both sides of the equation by 3.
2(-y+9)=5⋅(3)
Simplify 2(-y+9).
Apply the distributive property.
2(-y)+2⋅9=5⋅(3)
Multiply.
Multiply -1 by 2.
-2y+2⋅9=5⋅(3)
Multiply 2 by 9.
-2y+18=5⋅(3)
-2y+18=5⋅(3)
-2y+18=5⋅(3)
Multiply 5 by 3.
-2y+18=15
Move all terms not containing y to the right side of the equation.
Subtract 18 from both sides of the equation.
-2y=15-18
Subtract 18 from 15.
-2y=-3
-2y=-3
Divide each term by -2 and simplify.
Divide each term in -2y=-3 by -2.
-2y-2=-3-2
Cancel the common factor of -2.
Cancel the common factor.
-2y-2=-3-2
Divide y by 1.
y=-3-2
y=-3-2
Dividing two negative values results in a positive value.
y=32
y=32
y=32
The result can be shown in multiple forms.
Exact Form:
y=32
Decimal Form:
y=1.5
Mixed Number Form:
y=112
Solve for y (4y)/3+2(3-y)=5

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top